How to measure product differentiation - Franz Hackl; Michael Hölzl-Leitner; Dieter Pennerstorfer (Johannes Kepler University of Linz, Department of Economics, 2021)
In this article, we provide a novel measure of product differentiation by observing consumer search behavior directly. We track individual consumers in a price search engine and generate a measure of distance in product space, based on goods surveyed conjointly within individual search episodes. This metric performs well in an application to digital cameras as an example of complex products. Regression results show that differences in product characteristics are correlated with our measure of distance to a surprisingly high degree, and that prices are significantly lower if products have to compete with a larger number of close substitutes.
Keywords: D83; D43; L13; L63; 330; product differentiation; characteristic space; consumer search; price searchengine; clickstream